2019
DOI: 10.2196/15426
|View full text |Cite
|
Sign up to set email alerts
|

Group Sex Events Among Cisgender Men Who Have Sex With Men: Cross-Sectional and Longitudinal Survey Study to Explore Participation and Risk-Taking Behaviors

Abstract: BackgroundGroup sex events (GSEs) are common among cisgender men who have sex with men (MSM), pose a unique risk profile for HIV and sexually transmitted disease (STD) transmission, and may be on the rise, in part because of Web-based networking platforms. However, collecting data on GSEs can be challenging, and many gaps exist in our knowledge about GSE participation among MSM.ObjectiveThe objective of this study was to develop survey questions addressing aggregate and partner-specific group sex behaviors to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
(46 reference statements)
0
10
0
Order By: Relevance
“…Group sex, a sex event that involves more than two participants, has been considered a high-risk activity for the acquisition of HIV and other sexually transmitted infections (STIs) due to a greater number of partners affected by condomless sex ( 1 ). Previous studies have estimated about 27.2–34.8% of gay, bisexual and other men who have sex with men (MSM) had participated in at least one group sex event in the past 3 months ( 2 , 3 ). An exploratory study by Turek et al ( 4 ) reported 49% of 51 female sex workers (FSWs) had participated in at least one group sex event in the past 3 months.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Group sex, a sex event that involves more than two participants, has been considered a high-risk activity for the acquisition of HIV and other sexually transmitted infections (STIs) due to a greater number of partners affected by condomless sex ( 1 ). Previous studies have estimated about 27.2–34.8% of gay, bisexual and other men who have sex with men (MSM) had participated in at least one group sex event in the past 3 months ( 2 , 3 ). An exploratory study by Turek et al ( 4 ) reported 49% of 51 female sex workers (FSWs) had participated in at least one group sex event in the past 3 months.…”
Section: Introductionmentioning
confidence: 99%
“…There are few studies investigating group sex among FSWs. While most group sex studies have focused on MSM, other at-risk populations such as heterosexuals and FSWs have been understudied ( 2 , 3 ). Additionally, previous studies have predominantly examined the association between group sex participation and HIV/STI acquisition with few data on the details of sexual activities during the group sex event such as the size of the group sex event (i.e., the number of participants) and the sexual activities involved during group sex.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies investigating group sex focus on MSM, where the proportion of engaging in group sex within the past 3 months is estimated to be 27-35%. 4,5 However, there have been very limited group sex studies among other at-risk populations, such as heterosexuals. [4][5][6] A cross-sectional survey by Constantinou et al (2021) reported that 5% of 698 heterosexual men and women in Melbourne had participated in at least one group sex event within the past 3 months and found that heterosexuals who participated in group sex were over six times more likely to test positive for chlamydia, gonorrhoea or syphilis.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 However, there have been very limited group sex studies among other at-risk populations, such as heterosexuals. [4][5][6] A cross-sectional survey by Constantinou et al (2021) reported that 5% of 698 heterosexual men and women in Melbourne had participated in at least one group sex event within the past 3 months and found that heterosexuals who participated in group sex were over six times more likely to test positive for chlamydia, gonorrhoea or syphilis. 6 Furthermore, previous studies investigating mixed-gender group sex events have not studied the number of people involved in each group sex event, the sexual activities involved in group sex events and the practice of changing condoms between partners during group sex in details.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation